Development of flow cytometry technique for detection of thinning of peptidoglycan layer as a result of solvent production by Clostridium pasteurianum - Linhová, M; Patáková, P; Lipovský, J; Fribert, P; Paulová, L; Rychtera, M; Melzoch, K (Folia microbiologica, 2010)
Clostridium pasteurianum forms acetic and butyric acids in an initial growth phase, which is a typical feature of clostridial acetone-butanol fermentation where an initial accumulation of acids is followed by production of solvents 1-butanol, acetone and ethanol. The initiation of the solvent production coupled with endospore formation leads to decrease of cell-wall thickness; thinner cell wall is more resistant against solvents and dyes. These changes can be observed by the method based on adaptation of Gram staining. The cell wall of G+ bacteria allows the entry of hexidium iodide and rhodamine 123, whereas the outer membrane of G- bacteria does not allow the uptake and therefore G+ bacteria are stained with higher fluorescence intensity than G- bacteria. The ratio of fluorescence intensity (FI) to forward scatter (FSC) was determined to correspond to G+ bacteria when clostridia were producing less solvents. The significant drop of the ratio FI to FSC to the level corresponding to G- bacteria is detected after initiation of solvent production.
Keywords: genciánová violeť; Ethanol; Gentian Violet; aceton; Acetone; Staining and Labeling; Clostridium; průtoková cytometrie; n-butanol; Phenazines; Peptidoglycan; 1-Butanol; peptidoglykan; fenaziny; ethanol; Flow Cytometry; barvení a značení